Solve for a natural log of a+ natural log of b = natural log of a+b

Math
ln(a)+ln(b)=ln(a+b)
Use the product property of logarithms, logb(x)+logb(y)=logb(xy).
ln(ab)=ln(a+b)
For the equation to be equal, the argument of the logarithms on both sides of the equation must be equal.
ab=a+b
Solve for a.
Tap for more steps…
Subtract a from both sides of the equation.
ab-a=b
Factor a out of ab-a.
Tap for more steps…
Factor a out of ab.
a(b)-a=b
Factor a out of -a.
a(b)+a⋅-1=b
Factor a out of a(b)+a⋅-1.
a(b-1)=b
a(b-1)=b
Divide each term by b-1 and simplify.
Tap for more steps…
Divide each term in a(b-1)=b by b-1.
a(b-1)b-1=bb-1
Cancel the common factor of b-1.
Tap for more steps…
Cancel the common factor.
a(b-1)b-1=bb-1
Divide a by 1.
a=bb-1
a=bb-1
a=bb-1
a=bb-1
Solve for a natural log of a+ natural log of b = natural log of a+b

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top